Bodies as resistance: Claiming the political act of being oneself (2017)
The power of accepting ourselves begins by accepting our bodies. Poet, Activist, Author Sonya Renee Taylor is an author, poet, spoken word artist, speaker, humanitarian and social justice activist, educator, and founder of The Body is Not An Apology movement, an international movement and organization committed to radical self-love and body empowerment as the foundational tool for social justice and global transformation. Sonya’s work as an award winning Performance Poet, activist and transformational leader continues to have global reach. Sonya is a former national and international poetry slam champion, author, educator and activist who has mesmerized audiences across the US, New Zealand, Australia, Germany, England, Scotland, Sweden, Canada and the Netherlands as well as in prisons, mental health treatment facilities, homeless shelters, universities, festivals and public schools across the globe. http://www.sonya-renee.com
Producers: _:n22012
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; corps; cours; fem3300; militance; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; états-unis